Blood meal source influences starter pig performance - L J Kats; T L Weeden; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 144 weanling pigs (initially 14.1 lb and 24 d of age) was used to compare three different blood meal sources in starter diets. The three sources included spray-dried porcine, spray-dried bovine, and flash-dried bovine blood meal. Each diet contained 10% dried whey and 2.5% of one of the three blood meal sources. Diets were formulated to contain 1.25%lysine and .31% methionine. Pigs receiving diets containing either source of spray-dried blood meal had improved average daily gain and feed efficiency during the first 2 weeks of the experiment and the overall trial compared to pigs receiving diets containing the flash-dried source. No differences occurred in pig performance between the two spray-dried sources. Therefore, no apparent effects were due to species differences, but the blood meal must be spray-dried in order to optimize starter pig performance.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Blood meal; Performance